Dietary non-phytate phosphorus and phytase interaction affects growth performance, mineral transportation and metabolism in broiler chickens - Bingbing Ma; Yan Zhang; Mengyuan Liu; Chuanxin Shi; Yu Zhou; Mengyue Chen; Yuchun Chang; Hongxia Qu; Liao Zhang; Chunmei Zhang; Guanhua Chen; Jincheng Han (Poultry Science)
The interaction effects of dietary non-phytate phosphorus (NPP) and phytase on growth performance, mineral metabolism, and gene expressions of mineral transporters in broilers duodenum and kidney (0-3 weeks) were studied. The levels of NPP (0.45 %, 0.35 %, or 0.25 %) and phytase (0 or 2,500 FTU/kg) in the diets were applied in a 3 × 2 factorial arrangement to carry out rearing feeding strategies. Broilers received the diet containing 0.25 % NPP showed lower (P < 0.05) body weight gain (BWG), feed intake (FI), plasma calcium (Ca) and phosphorus (P) levels, bone attributes, and higher (P < 0.05) mortality rate than those of broilers fed diets containing 0.45 % NPP alone or in combination of phytase, 0.35 % NPP or 0.25 % NPP in combination of phytase. Significant interactions (P < 0.05) of phytase and NPP were found in BWG, FI, bone attributes, plasma Ca and P levels, and mortality rate of broiler. Broilers received the diet containing 0.25 % NPP had higher (P < 0.05) mRNA expressions of nuclear vitamin D receptors (nVDR), Calbindin-D28k (CaBP-D28k) and Plasma membrane Ca ATPase 1b (PMCA1b) in duodenum, mRNA expressions of CaBP-D28k and sodium-dependent phosphate cotransporters type IIa (NaPi-IIa) in kidney, and liver 25-hydroxylase mRNA expression than those of broilers fed diets containing 0.45 % NPP alone or in combination of phytase, 0.35 % NPP or 0.25 % NPP in combination of phytase. The interaction of NPP and phytase significantly affected (P < 0.05) the mRNA expressions of nVDR, CaBP-D28k and PMCA1b in duodenum, the mRNA expressions of CaBP-D28k and NaPi-IIa in kidney, and liver 25-hydroxylase mRNA expression. Dietary phytase supplementation improved growth performance, bone attributes, and absorption of Ca and P even if dietary NPP level dropped to 0.25 %.